American scream : Allen Ginsberg's Howl and the making of the Beat Generation - Raskin, Jonah, 1942- (University of California Press, 2004)
Written as a cultural weapon and a call to arms, Howl touched a raw nerve in Cold War America and has been controversial from the day it was first read aloud nearly fifty years ago. This first full critical and historical study of Howl brilliantly elucidates the nexus of politics and literature in which it was written and gives striking new portraits of Allen Ginsberg, Jack Kerouac, and William Burroughs.